2013
DOI: 10.1039/c3sm51061a
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of ethosome-like catanionic vesicles by water-soluble polymers: ethanol and cholesterol effects

Abstract: Ethosome-like catanionic vesicles are vesicular carriers prepared by using ion-pair amphiphiles (IPAs) and relatively high concentrations of ethanol through a semispontaneous process for dermal drug delivery.In this work, the effects of ethanol and cholesterol on the polymer configuration and vesicular membrane rigidity (or hydrophobicity) and therefore the gelation of the as-prepared ethosome-like catanionic vesicles by water-soluble polycations with and without hydrophobic modification (HMP + and P + ), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The stability can be improved inter-vesicular using additives such as charged amphiphiles or polymers that increase the electrostatic or steric repulsion among IPA vesicles [ 15 , 16 , 17 ]. Meanwhile, additives such as cholesterol have been shown to improve the intra-vesicular stability of IPA vesicles via strengthening the mechanical properties of the vesicular bilayer [ 18 , 19 , 20 , 21 , 22 ]. The vesicles prepared from biomimetic IPAs are therefore good candidates as phospholipid substitutes and have great potentials in various applications such as cosmetics and drug carriers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stability can be improved inter-vesicular using additives such as charged amphiphiles or polymers that increase the electrostatic or steric repulsion among IPA vesicles [ 15 , 16 , 17 ]. Meanwhile, additives such as cholesterol have been shown to improve the intra-vesicular stability of IPA vesicles via strengthening the mechanical properties of the vesicular bilayer [ 18 , 19 , 20 , 21 , 22 ]. The vesicles prepared from biomimetic IPAs are therefore good candidates as phospholipid substitutes and have great potentials in various applications such as cosmetics and drug carriers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…By the way, film formulations cannot be obtained with ethosome suspensions. The effect of ethanol on gelation of ethosome was reported by Chiu et al (2013). It was concluded that, ethanol mainly affects the gelation through its influence on the solution dielectric constant and therefore the polymer chain configuration and for ethosomelike catanionic vesicles with higher ethanol concentrations; a larger amount of gelator is needed for the formation of a gel phase.…”
Section: Preparation and Characterization Of Formulationsmentioning
confidence: 93%
“…The physical stability of catanionic vesicles could be significantly enhanced by the presence of CHOL in the vesicular bilayer structures 10,17,18 .…”
mentioning
confidence: 96%
“…Moreover, while the increase in CHOL concentration resulted in increase in the encapsulation efficiency of a hydrophobic drug for DeTMA-DS decyltrimethylammoniumdodecylsulfate and DeTMA-TS decyltrimethylammoniumtetradecylsulfate, CH 3 CH 2 9 N CH 3 3 -CH 3 CH 2 13 SO 4 systems 17,18 , the increase in CHOL concentration resulted in decrease in the encapsulation efficiency of the same drug for dodecyltrimethylammonium-dodecylsulfate DTMA-DS, CH 3 CH 2 11 N CH 3 3 -CH 3 CH 2 11 SO 4 system 18 .…”
mentioning
confidence: 99%